Metabolic response of Chlorella vulgaris to a transient thermal environment for supporting simultaneous air revitalization and thermal control in a crewed habitat. (October 2021) - Matula, Emily E.; Nabity, Dr James A.
Abstract: Implementing multifunctional bioregenerative technologies may provide mission carbon loop closure while simultaneously addressing multiple environmental control and life support system requirements. This paper proposes using water-based algal medium for thermal control of the spacecraft cabin, while taking advantage of the algae's photosynthetic activity for air revitalization. Consequently, this could expose the algal culture to transient thermal environments fluctuating between +4 °C and +30 °C, in the span of minutes, reflecting the operation of the International Space Station (ISS) internal thermal control and cabin system. This paper presents an initial investigation of the metabolic response of Chlorella vulgaris to transient environmental temperatures, reflecting temperature ranges and cycling frequency of the ISS cooling loop (+9 °C to +27 °C, 30 min). The constant 19 °C control represented the time-averaged temperature of the cycled condition. Growth and acclimation were observed in both tested conditions through pH, dissolved oxygen, optical density, and photosynthetic quantum yield measurements. However, there was significant reduction in the oxygen production rate, measured pH, and optical density for the cycled temperature condition when compared to the control (cycled temperature = 0.95 gO2 L −1 d −1, pH = 6.75, OD = 0.05; control = 1.17 gO2 L −1 d −1, pH = 8.20, OD = 0.08). No significant reduction in growth rate or photosynthetic quantum yield were recorded between the two tested conditions. Growth rate of the cycled temperature condition reflected those of psychrotolerant algae, suggesting some amount of culture acclimation to the rapidly dynamic environment. Results suggest that while C. vulgaris was viable within the tested temperature environment reflecting the ISS thermal control loop and cabin, there was a measurable reduction in the oxygen production rate. Highlights: A photobioreactor for simultaneous spacecraft thermal control and air revitalization. Chlorella survive extreme thermal profile of spacecraft thermal control. Oxygen production rate significantly less for cycled temperature algae. Minimal cellular stress documented for steady and cycled temperature algae.